A boost current source inverter based generator-converter topology for direct drive wind turbines - Singh, Akanksha (Kansas State University, 2017)
In this dissertation, a new topology for Direct-Drive Wind Turbines (DDWTs) with a new power electronics interface and a low-voltage generator design is presented. In the presented power electronics interface, the grid - side converter is replaced by a boost Current Source Inverter (CSI) which eliminates the required dc-bus capacitors resulting in an increase in the lifetime of DDWTs. The inherently required dc-link inductor for this topology is eliminated by utilizing the inductance of the Permanent Magnet Synchronous Generator (PMSG). The proposed three-phase boost CSI is equipped with Reverse-Blocking IGBTs (RB-IGBT) and the Phasor Pulse Width Modulation (PPWM) switching pattern to provide a 98% efficiency and high boost ratios ([superscript V]LL/V[subscript dc]) up to 3.5 in a single stage. In this dissertation, Phasor Pulse Width Modulation (PPWM) pattern for the boost – CSI is also modified and verified through simulation and experimental results. In order to realize potential capabilities of the boost inverter and to assist its penetration into renewable energy systems, the boost inverter dynamic behaviors are studied in this dissertation. Then, the developed models are verified using circuit simulations and experiments on a laboratory-scale boost – CSI equipped with RB-IGBTs. The developed dynamic models are used to study the stability of the boost – CSI through root locus of small signal poles (eigenvalues) as control inputs and load parameters vary within the boost inverter's operating limits. The dynamic models are also used to design the control schemes for the boost – CSI for both stand-alone and grid-tied modes of operation. The developed controllers of the boost – CSI are verified through simulation and experimental results. In this dissertation, the boost – CSI steady-state characterization equations are also developed and verified. The developed boost – CSI is used to replace the grid - side converter in a DDWT. A reliability analysis on the power electronics interface of an existing and developed topology is presented to demonstrate the increase in the mean time between failures. The boost – CSI enables conversion of a low dc voltage to a higher line-to-line voltage enabling the implementation of a low-voltage generator. This further enables a reduction in the number poles required in DDWT generators. The feasibility of the presented low-voltage generator is investigated through finite element computations. In this dissertation, a 1.5MW low-voltage generator designed for the proposed topology is compared with an existing 1.5MW permanent magnet synchronous generator for DDWTs to demonstrate the reduction in the volume, weight, and amount of permanent magnet materials required in the generator. The feasibility of the developed system is supported by a set of MATLAB/Simulink simulations and laboratory experiments on the closed-loop stand-alone and grid-tied systems.
Keywords: Electrical engineering; Power electronics converters; Wind power generation; Direct drive wind turbine topology